EFFECTIVENESS OF AQUAPONICS SYSTEM FOR TILAPIA CULTURE (Oreochromis niloticus) WITH RECIRCULATION SYSTEM - Sopiandi; Marzuki, Muhammad; Setyono, Bagus Dwi Hari (Jurnal Media Akuakultur Indonesia, 2022)
Tilapia is a leading commodity in Indonesia, in its cultivation the availability of water is one of the obstacles for cultivators, one of the efforts made is by cultivating aquaponics and recirculation systems. This study aims to determine the effectiveness of the aquaponics system on the survival and growth of tilapia (Oreochromis niloticus) fry with a recirculation system. The research method used a completely randomized design (CRD) using four treatments and three replications, namely P1 (without plants) P2 (lettuce plants), P3 (caisim plants), P4 (kangkung plants) then further tests were carried out using Analysis of Variance (ANOVA). ). Research parameters include absolute weight (BM), absolute length (PM), specific growth rate (SGR), survival rate (SR) and water quality. The results of this study indicate that the aquaponics system for tilapia cultivation with a recirculation system has a significant effect on the growth and survival of tilapia.